2015
DOI: 10.1007/s12098-015-1924-y
|View full text |Cite
|
Sign up to set email alerts
|

Anemia, Iron Deficiency and Iodine Deficiency among Nepalese School Children

Abstract: Iron deficiency and anemia are common in Nepalese children, whereas, iodine nutrition is more than adequate. Low urinary iodine excretion was common in iron deficiency and anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 14 publications
1
20
3
1
Order By: Relevance
“…There are limited data on iodine status during pregnancy in Nepal, however, in school children there has been continuous improvement in iodine nutrition. 1,[8][9][10][11] In one study, Schulze et al observed mild iodine deficiency in pregnant and lactating women of rural southern plains (Terai region) of Nepal. 13 In a study in India, median UIC was 203 μg/L and 211 μg/L at 17 and 34 weeks of pregnancy respectively, whereas in another study, median (range) UIC in the first, second, and third trimesters was 285 μg/L (102-457), 318 μg/L (102-805), and 304 μg/L (172-859) respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are limited data on iodine status during pregnancy in Nepal, however, in school children there has been continuous improvement in iodine nutrition. 1,[8][9][10][11] In one study, Schulze et al observed mild iodine deficiency in pregnant and lactating women of rural southern plains (Terai region) of Nepal. 13 In a study in India, median UIC was 203 μg/L and 211 μg/L at 17 and 34 weeks of pregnancy respectively, whereas in another study, median (range) UIC in the first, second, and third trimesters was 285 μg/L (102-457), 318 μg/L (102-805), and 304 μg/L (172-859) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…17 Universal salt iodization has been the most common strategy of eliminating iodine deficiency in landlocked countries, and this been successful in Nepal with increasing number of households consuming adequately iodized salt and median UIC among school children is rising. 1,19 Thyroid dysfunction has been observed as the most frequent endocrine disorder in pregnant women. 5 We observed thyroid dysfunction in 19 (20.65%) pregnant women and the most common dysfunction was subclinical hypothyroidism (18,19.56%) when the upper normal cutoff value for TSH was taken 6.16 mIU/L.…”
Section: 15mentioning
confidence: 99%
“…This community based study reported 34.5 % and 43.4 % school children (age: 6-13 y) to have anemia and iron deficiency, respectively [1].…”
mentioning
confidence: 88%
“…Khatiwada et al evaluated the prevalence of IDA in children in eastern Nepal [1]. This community based study reported 34.5 % and 43.4 % school children (age: 6-13 y) to have anemia and iron deficiency, respectively [1].…”
mentioning
confidence: 99%
“…Nepal has been continuously improving iodine nutrition after starting universal salt iodization program. A number of studies particularly in eastern Nepal show promising results in improvement of iodine deficiency as revealed by increase in median urinary iodine concentration (UIC) of school children [6][7][8]. However, there are also concerns about excess iodine intake in such population [9].…”
Section: Introductionmentioning
confidence: 99%